Diaspora and Implementation of Sheikh Yusuf al-Makassarī’s Religious Moderation Teachings in South Sulawesi and Kalimantan - Sahib, Muzdalifah; Irnawati, Irnawati; Sahib, Muh. Amin; Asiah, Nur; Sahib, Nur Faizah; Jappie, Saarah (Jurnal Adabiyah, 2024)
Sheikh Yusuf al-Makassarī (1626-1699) is a worldwide figure from Gowa-Makassar, South Sulawesi, Indonesia, a reformer in the Islamic mystical world and a moderate ṣứfī whose teachings spread among his followers up today. This research investigates the diaspora and dissemination of Sheikh Yusuf al-Makassarī’s teachings on religious moderation in South Sulawesi and Kalimantan. Employing a qualitative descriptive method and a phenomenological approach, the study seeks to elucidate the process of diaspora development, assess the perceptions of al- Makassarī’s followers, especially Ṭarīqa Khalwatiyya Yusufiyya followers regarding religious moderation, and analyze the implementation of his teachings. The findings of this research reveal that the diaspora of al-Makassarī’s religious moderation teachings has emanated and proliferated from Gowa through three teachers (murshids) and his descendants (1940s-2022), notably Sheikh K.H. Sahib Sultan (d.2022), and his parents across South Sulawesi and Kalimantan, extending even to the entirety of the archipelago. Throughout four to five generations, the diaspora has become entrenched through these murshids. While a significant portion of al-Makassarī’s followers may remain unfamiliar with the term "religious moderation," his teachings have been effectively implemented, resulting in improved social well-being, enhanced safety, and increased tranquility. Notably, these adherents distance themselves from any form of religious extremism. This research underscores the substantial impact of the ṣūfī Order (Ṭarīqa) in mitigating radicalism and terrorism in Indonesia. Consequently, understanding and practicing al-Makassari’s teachings on religious moderation emerge as crucial for fostering a safer, more prosperous, and peaceful future for Indonesians. الملخص الشيخ يوسف المكساري (1626-1699) شخص مشهور عالمياً من غووا مكسار، سولاويسي الجنوبية، إندونيسيا، مجدّد في عالم التصوف الإسلامي، وصوفي وصطي تنتشر تعاليمه بين أتباعه حتى اليوم. هذا البحث يركز على انتشار وتنفيذ تعاليم الوسطية الدينية للشيخ يوسف المكاسري في سولاويسي الجنوبية وكاليمانتان. ويستخدم الباحثون فيه منهجًا نوعيًا وصفيًا ومدخلا ظاهريًا لمعرفة العملية في تطوير الانتشار، وتقييم تصور أتباع المكاسري، خاصة أتباع الطريقة الخلوتية يوسوفية حول الوسطية الدينية وتحليل تنفيذ تعاليمه. أظهرت النتائج على أن تعاليم الوسطية الدينية للمكاسري قد تم تطوير وانتشارها من غووا من قبل ثلاثة مرشد وأحفادهم (1940-2022)، وخاصة الشيخ الحاج صاحب سلطان (المتوفى سنة 2022) مع والديه في جميع أنحاء سولاويسي الجنوبية وكاليمانتان، وحتى في جميع أنحاء الأرخبيل نوسانتارا. من خلال هؤلاء المرشدين الثلاث، قد بلغ تطور الانتشار مابين أربعة إلى خمسة أجيال. على الرغم من أن معظم أتباعه لا يزالون غير معتادين على مصطلح الوسطية الدينية، إلا أن تعاليم المكاسري قد تم تنفذها جيدا بشكل عام، وتجعل حياتهم الاجتماعية أفضل في رفع الرفاهية الاجتماعية والأمن والاطمئنان. إنهم بعيدون عن أن يكونوا فوضويين. هذا البحث يركز على الأثر الجوهري للطريقة الصوفية في درء التطرف والإرهابية في إندونيسيا. فمن المهم معرفة وممارسة تعاليم الوسطية الدينية للمكاسري حتى يتمكن الشعب الإندونيسي من العيش بأمان ورخاء وسلام. الكلمة الرئيسية: تعاليم الوسطية الدينية، انتشار، تنفيذ، الشيخ يوسف المكسري Abstrak Syeikh Yusuf al-Makassarī (1626-1699) adalah seorang tokoh terkenal dunia, seorang pembaru dalam dunia mistik Islam sekaligus seorang shứfī moderat yang ajarannya tersebar di kalangan para pengikutnya hingga saat ini. Penelitian ini menyelidiki diaspora dan penyebaran ajaran Syekh Yusuf al-Makassarī tentang moderasi beragama di Sulawesi Selatan dan Kalimantan. Dengan menggunakan metode deskriptif kualitatif dan pendekatan fenomenologis, penelitian ini berupaya menjelaskan proses perkembangan diaspora, menilai persepsi pengikut al-Makassarī, khususnya pengikut Tariqat Khalwatiyyah Yusufiyyah mengenai moderasi beragama, dan menganalisis implementasi ajarannya. Temuan penelitian ini mengungkapkan bahwa diaspora ajaran moderasi beragama al-Makassarī terpancar dan menjamur dari Gowa melalui tiga orang guru (mursyid) dan keturunannya (1940-an-2022), khususnya Syeikh K.H. Sahib Sultan (w. 2022), dan kedua orang tuanya hingga tersebar melintasi Sulawesi Selatan dan Kalimantan, bahkan hingga ke seluruh nusantara. Selama empat hingga lima generasi, diaspora telah mengakar melalui para mursyid ini. Meskipun sebagian besar pengikut al-Makassarī mungkin masih asing dengan istilah "moderasi beragama", ajarannya telah diterapkan secara efektif, sehingga menghasilkan peningkatan kesejahteraan sosial, peningkatan keamanan, dan peningkatan ketenangan. Khususnya, para penganutnya menjauhkan diri dari segala bentuk ekstremisme agama. Penelitian ini menggarisbawahi dampak substansial Tarekat ṣūfī (Ṭarīqa) dalam mitigasi atau mengurangi resiko radikalisme dan terorisme di Indonesia. Oleh karena itu, memahami dan mengamalkan ajaran al-Makassarī tentang moderasi beragama menjadi hal yang penting untuk menciptakan masa depan yang lebih aman, sejahtera, dan damai bagi masyarakat Indonesia. ​Kata Kunci : Ajaran Moderasi Beragama; Diaspora; Implementasi; Syekh Yusuf al-Makassarī